Surgical Management of Anterior Glottic Webs - Kuo, I-Chun; Rutter, Michael (Frontiers in Pediatrics, 2020)
Congenital webs are rare and represent <5% of all congenital laryngeal anomalies. They are usually a partial laryngeal atresia rather than a true web, and present as a thick and fibrotic web with subglottic extension and associated subglottic stenosis. All patients with a congenital anterior glottic web should be evaluated for chromosome 22q11.2 deletion syndrome. Management strategies are mainly based on the severity of airway obstruction and the anatomical extension of the webs. Simple division of the web endoscopically may be adequate for rare thin webs, however, an open approach is usually warranted for thick glottic webs regardless of Cohen grades. Open repair can be either with keel placement or reconstruction of the anterior commissure.